In situ monitoring of PVDF ultrasound transducers under gamma irradiation. Issue 2 (2nd April 2020) - Kelley, T.; Hutchings, K.; Jenkinson, M.; Dawson, I.; Krawec, K.; Miyagawa, P. S.; Kern, J.H.; Edge, R.
ABSTRACT: Ultrasonic transducer (UT) systems are used for non-destructive testing and evaluation across a wide range of industries. In the nuclear industry, radiation damage of the UTs can lead to performance degradation or even complete failure. We have investigated the radiation resilience of a new piezo-polymer (PVDF) UT design. The irradiations were performed in a Cobalt-60 gamma facility with total ionising doses up to 10.5 MGy. Continuous pulse-echo measurements were taken in-situ allowing the performance as a function of time to be monitored. In addition to the UT irradiations and measurements, high fidelity Monte Carlo particle transport simulations were performed to study the radiation environments and the ionising dose profiles within the devices under test. These dose profiles were used to gain insight into the behaviour of PVDF under irradiation. Results show that all sensors were able to withstand the doses achieved without suffering complete failure, with the best performing device only losing 47% of its initial amplitude. Dose profiles for the PVDF show piezoelectric performance to increase by up to 7% at doses around 500 kGy after which performance was found to drop linearly at a rate of between 6.5% and 10% per MGy.